Kurdish Studies Archive : Vol. 9 No. 2 2021 - Bruinessen, Martin van, (Middle East and Islamic Studies E-Books Online, Collection 2025., 2021)
Kurdish Studies Archive publishes the content of volumes 1 to 10 of Kurdish Studies . This interdisciplinary and peer-reviewed journal was dedicated to publishing high-quality research and scholarship. Since 2023 the journal has been continued as the new Kurdish Studies Journal , published by Brill, and focuses on research, scholarship, and debates in the field of Kurdish studies in a multidisciplinary fashion covering a wide range of topics including, but not limited to, economics, history, society, gender, minorities, politics, health, law, environment, language, media, culture, arts, and education.